The Model of cross-industrial innovation in the development of clusters: international practice - Alzhanova, F.G.; Lashkareva, O.V. (BUKETOV BUSINESS REVIEW, 2017)
The article describes a model of cross-industrial innovation as a result of cross-functional interactions between different areas of knowledge and revealed its contrast to the linear model and the model of open innovation. It is shown that the basis of the appearance of the model cross-innovation is an objective process of strengthening the multidisciplinary nature of knowledge and technology, the penetration of traditional, mature technologies to new markets in a new way; complexity of ethical and social issues in the course of the growing influence of new technologies. The experience of the principles of cross-innovations implementation in foreign countries and individual companieswas reviewed. On the basis of the intensity of mergers and acquisitions, joint ventures and alliances, the availability of patents in innovation and cross-cross-linkages with other sectors of the 10 regions of the growing industries were identified that form the basis of clusters, built on the cross-ties. The most dynamic intersectoral links demonstrate the industry of packing materials and bio pharmacy. The expediency of innovation clusters creation based on the model of cross-industrial innovation was proved. The advantages of the implementation of cross-innovation models in clusters in the form of the emergence of radical innovation and new industries reduce risk, reduce conflicts over market share, etc were shown.